AUTHORIAL IDENTITY AND AUTOBIOGRAPHICAL WRITING OF MICHAEL ONDAATJE: THEORETICAL ASPECTS - Khoma, Vasylyna (Іноземна філологія, 2022)
The present paper examines the main theoretical aspects of literary autobiography. To achieve this aim, the general context of modern biographical writing development was studied, and critical articles, reviews and researches, both Ukrainian and foreign, were analyzed. Additionally, in order to defi ne biography and autobiography, intersection points of autobiography and postmodernism, as well as the peculiarity of fact and fi ction interrelation in postmodern autobiographical and memoir literature have been revealed. The methodology of the article is based on exploring the aesthetic and literary component of biographical works, namely on studies by P. Holden, P. Lejeune and P. Ricoeur’s identity analysis of “Oneself as Another”. Moreover, due to the fact that it is very important to assess the writer’s identity in two ways – from the point of view of the Other and from the point of view of the person’s inner Self – and to provide an understanding of how the past life experience of writers aff ects their current worldview and literary works, the biographical method has been chosen. Since autobiographical writing and memoirs reproduce the process of author’s self-refl ection about himself/herself and others, the particular attention is focused on the concepts of identity and autobiographical memory of the author. Accordingly, life and narrative identity correlation of the author’s fi gure constitute a relevant issue for the analysis of autobiographies and memoirs. It is shown that the autobiography of Michael Ondaatje, a Sri Lankan-born Canadian writer, is connected with the principles of postmodern and postcolonial literature. Finally, referring to interviews with the writer and his works of fi ction, as well as taking into account critical studies of his literary works, it is concluded that his authorial identity combines the features of the dual postcolonial identity of a Canadian cosmopolitan writer who preserves the cultural memory of Sri Lanka.